PROJECT-BASED LEARNING FOR CRITICAL THINKING DEVELOPMENT: A LITERATURE REVIEW - Danar Widiyanta; Andi Is'af Khalilullah; Farida Asy'ari (Adisam Publisher, 2026)
The development of 21st-century education emphasizes the importance of critical thinking skills as essential competencies for students in facing complex real-world challenges. Project-Based Learning (PBL) has emerged as a student-centered instructional approach that engages learners in authentic problem-solving through collaborative and inquiry-based activities. This study aims to examine the role of Project-Based Learning in improving students’ critical thinking skills through a literature review approach. Data were collected from reputable academic publications indexed in international databases and analyzed using content analysis to identify research trends, key findings, and research gaps related to PBL implementation. The findings indicate that PBL positively contributes to the development of critical thinking skills by promoting active learning, collaboration, and reflective problem-solving experiences. However, the effectiveness of PBL depends mainly on the quality of instructional design, teacher facilitation, and integration within the curriculum. Challenges related to implementation readiness and assessment strategies remain important considerations. Therefore, future development of project-based instruction should integrate sound pedagogical planning and technological support to maximize learning outcomes and foster sustainable development of critical thinking in education.